1984
DOI: 10.1007/bf00119789
|View full text |Cite
|
Sign up to set email alerts
|

Inertial subrange correlation between temperature and humidity fluctuations in the unstable surface layer above vegetated terrains

Abstract: Observations of the temperature-humidity cospectrum and correlation spectrum were made with a cold platinum wire and a Ly-a hygrometer at 3.7 and 10 m above vegetated surfaces during unstable atmospheric conditions. It was found theoretically that a separation 6 between the temperature and humidity sensors causes a drop-off of the correlation spectrum at wavenumbers > 0.3 6-'. The observed drop-off follows the theoretical one reasonably well. Measurements made with the temperature sensor placed in the center o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For example, McBean's (1971) temperature spectra showed a distinct inertial-convective subrange; but his humidity spectra, though having levels similar to his t spectra at l οω frequency, fell off much more rapidly than f-5"3 at high frequency. Kohsiek (1984) made similar observations; his t spectra went as f-5/3 at high frequency, but his q spectra fell off somewhat more rapidly. The temperature and humidity spectra Schmitt et al (1979) measured over Minnesota farmland behaved, generally, like the Kansas temperature spectra; but, as with their oceanic measurements, the humidity spectra had an unusual hump near fz/U = 1.…”
Section: Temperature and Humidity Spectramentioning
confidence: 60%
“…For example, McBean's (1971) temperature spectra showed a distinct inertial-convective subrange; but his humidity spectra, though having levels similar to his t spectra at l οω frequency, fell off much more rapidly than f-5"3 at high frequency. Kohsiek (1984) made similar observations; his t spectra went as f-5/3 at high frequency, but his q spectra fell off somewhat more rapidly. The temperature and humidity spectra Schmitt et al (1979) measured over Minnesota farmland behaved, generally, like the Kansas temperature spectra; but, as with their oceanic measurements, the humidity spectra had an unusual hump near fz/U = 1.…”
Section: Temperature and Humidity Spectramentioning
confidence: 60%
“…The correlation coefficient (r) between temperature and humidity fluctuations over simple surfaces has been observed to be near unity for neutral and unstable conditions (Wesely and Hicks, 1978;Wyngaard et al, 1978;Kohsiek, 1984) implying similarity in the to.3…”
Section: Estimates Using a Flux/gradient Relationshipmentioning
confidence: 99%
“…A number of investigators (Swinbank and Dyer, 1967;Phelps and Pond, 1971;McBean and Miyake, 1972;Thorpe et al, 1973;Friehe et al, 1975;Wesely and Hicks, 1978;Wyngaard et al, 1978) have shown that temperature and humidity fluctuations are highly correlated at frequencies corresponding to the flux-carrying eddies over uniform, warm, wet surfaces, presumably because the surface appears as a uniform source of both heat and water vapor that are mixed upward by practically the same turbulent wind motions. Indeed, this strong correlation can extend to greater frequencies (Kohsiek, 1984). If the high degree of correlation exists between temperature (or humidity) and other scalar quantities, especially at the frequencies of flux-carrying eddies, then the considerable information available on relationships of fluxes to variances for temperature and humidity is probably also applicable to many other scalar quantities.…”
Section: Nature Of Scalar Fluctuationsmentioning
confidence: 99%
“…The equations used in the adjustments are described by Hicks (1972), except that the adjustments for phase shift caused by sensor separation along the mean flow are omitted. In principle, this approach to accounting for sensor separation should produce adjustments equivalent to those produced with the procedures described by Kohsiek (1984) for sensors separated in a direction transverse to the mean flow. A comparison of the two approaches, however, reveals that Kohsiek's adjustments have a slightly larger effect.…”
Section: Nature Of Scalar Fluctuationsmentioning
confidence: 99%